2011
DOI: 10.1007/s00381-011-1632-5
|View full text |Cite
|
Sign up to set email alerts
|

Success of pure neuroendoscopic technique in the treatment of Sylvian arachnoid cysts in children

Abstract: Our results suggest that "pure neuroendoscopic" approach can be used safely in the management of SACs in children. We recommend at least two fenestration sites for an effective marsupialization of the cyst within the basal cisterns. In pediatric cases, the use of a small diameter rigid endoscope allows to reach safely the planned target areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 22 publications
3
25
0
1
Order By: Relevance
“…Options of surgical techniques are craniotomy and cyst wall excision,[214] cystoperitoneal or cystoventricular shunt or endoscopic fenestration. [1011131520] In agreement with a study by Cincu et al ., it was concluded that communicating the cyst with the ventricular system or basal cisterns appears to offer the best chance of a success in the treatment of arachnoid cysts. [5] Nonetheless, this case report highlights the importance of knowing further major connectional anatomical structures that lie between the cyst, ventricle, or cistern before embarking on definitive endoscopic surgery.…”
Section: Discussionsupporting
confidence: 91%
“…Options of surgical techniques are craniotomy and cyst wall excision,[214] cystoperitoneal or cystoventricular shunt or endoscopic fenestration. [1011131520] In agreement with a study by Cincu et al ., it was concluded that communicating the cyst with the ventricular system or basal cisterns appears to offer the best chance of a success in the treatment of arachnoid cysts. [5] Nonetheless, this case report highlights the importance of knowing further major connectional anatomical structures that lie between the cyst, ventricle, or cistern before embarking on definitive endoscopic surgery.…”
Section: Discussionsupporting
confidence: 91%
“…12,54,74,76,78,88,94 However, there are no studies evaluating a large series of adults with untreated arachnoid cysts who have undergone clinical and imaging followup. Although arachnoid cysts may be treated surgically by endoscopic fenestration, 24,31,48,67,79,91,105 craniotomy for fenestration, 15,31,55,79 or shunt placement, 15,34,67,73,79 these operations are associated with potential morbidity. 24,39,48,55,57,58,79,80,85,105 A better understanding of the prevalence and natural history of these cysts in adults may lead to better definition of surgical indications for adult patients with arachnoid cysts discovered on imaging.…”
mentioning
confidence: 99%
“…Therefore, endoscopy is a safe and effective therapeutic modality for all kinds of IAC, especially those located in the suprasellar and quadrigeminal regions as well as the posterior fossa. [8,9,10] Only three patients had undergone this method, and only one patient had this surgical treatment after we had endoscopy. We chose cystoperitoneal shunting for the middle-fossa IAC with a significant volume to avoid over drainage and fierce variation in intracranial pressure, lessen the occurrence rate of epidural or subdural hematoma, and fully informed the possibility of reoperation for alternating the shunt device.…”
Section: Discussionmentioning
confidence: 98%